Struktur dan Geometri Cekungan Oil Shale di Daerah Taluk, Riau, Berdasarkan Metode Gaya Berat - Panjaitan, Saultan (Jurnal Geologi dan Sumberdaya Mineral, 2006)
Gravity anomaly in Taluk area can be grouped into: a. high gravity anomaly of 19 mgal to 55 mgal showing the Pretertiary high faulted to the surface. b. low gravity anomaly of 19 mgal to - 25 mgal predicted as a sedimentery basin. Distribution of oil shale of Keruh Formation is very limited. However, based on the result of investigation using gravity method, the subsurface basin configuration where the Keruh Formation occured is marked by a low anomaly from 0 to – 8 mgal and is situated in fault contact of the Kuantan Formation covered by yonger rock. Anticlines comprising : anticlines of Jakai, Taluk, and Lipai were formed by residual anomaly of 0 mgal to 11 mgal. The Jakai anticlines shows more extended dimension. While the Emas and Logen anticlines have much smaller dimension with lower anomaly. Muarapantai and Kualanangau anticlines in the northeast part have never been drilled. Anticline of Muarapantai was assumed to contain oil shale in TBS. Keywords: Taluk ,oil shale, basin ,anticlines, fault, anomaly,gravity